Hypogonadism and anemia in an athlete - Korsten-Reck, U.; Seufert, J.; Dickhuth, H.-H.; Schumacher, Y. O.; König, D. (International Journal of Sports Medicine, 2012)
We report the case of a highly trained endurance athlete (22-year-old) who developed anemia (Hb 9.5 mg/dl) over a period of 6 months. Iron deficient or haemolytic anemia, as well as chronic loss of blood, were excluded. Further, laboratory analyses revealed that this athlete exhibited very low levels of testosterone due to a partial hypogonadotropic hypogonadism. Following testosterone supplementation, red blood cell indices improved. Although hypogonadotropic hypogonadism is well known to be associated with reduced hematopoesis, it rarely causes anemia in athletes. This should be considered as a possible cause for anemia. Extreme training, unbalanced nutrition or the combination of both, have been shown to be causally involved in the development of secondary hypogonadotropic hypogonadism.